[TELEX REGARDING INFLIGHT AIR QUALITY STUDIES AND THE INTERNATIONAL FLIGHT ATTENDANTS ASSOCIATION] - ROBINSON,JB (Tufts Archival Research Center, 2007)
Marginalia; Telex proposing suggestions for the Philip Morris/International Flight Attendants Association meeting. Requests permission for Philip Morris to be a corporate sponsor of the 7th World Congress of the IFAA. Suggests conducting in flight air quality studies (IFAQ) on the part of Philip Morris to be published by the IFAA to address workplace smoking concerns. Describes some of the procedural aspects of the research, including the use of briefcase samplers and personal nicotine monitors.